2017
DOI: 10.1590/s0104-40362017002501111
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of non-formal sexual education strategies for adolescent girls: the case of Tanzania

Abstract: This article proposes a critical look at the non-formal education strategies, which have been conducted mainly in Dar es Salaam, Tanzania, by four nongovernmental organizations, in order to provide sexual education to girls between the ages of 12 and 16, showing the role played by the civil society in contradicting the school conservatism. Clear trends emerged from this study to indicate that sexual risky behaviours, unintended pregnancies, and HIV transmission among adolescent girls are closely related to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…However, evaluations of SRH education curricula in sub-Saharan Africa have been inconclusive on their impact in reducing risky sexual behaviors and the incidence of STIs/HIV among young adults [32,35]. The SRH education curriculum that was introduced in Tanzania in primary schools during the early 2000's to help with the control of the HIV pandemic has been important for educating adolescents in primary and secondary schools, but its main challenge has been the inability of many teachers to deliver the message and topics clearly [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evaluations of SRH education curricula in sub-Saharan Africa have been inconclusive on their impact in reducing risky sexual behaviors and the incidence of STIs/HIV among young adults [32,35]. The SRH education curriculum that was introduced in Tanzania in primary schools during the early 2000's to help with the control of the HIV pandemic has been important for educating adolescents in primary and secondary schools, but its main challenge has been the inability of many teachers to deliver the message and topics clearly [36].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst Mkumbo et al showed that the majority of urban and rural teachers in Tanzania were supportive of SRH education teaching [13], Cardoso and Mwolo noted an ineffective inclusion of sensitive sexuality matters in the school curricula and inadequate resources [36].…”
Section: Discussionmentioning
confidence: 99%
“…Further, participants felt they needed to know more about sexual feelings, emotions and relationships, safer sex, how to be able to say 'No' and how to use a condom correctly; such information may indicate that during such an encounter probably even a condom or other protective means to STIs/HIV and/or pregnancy were not used. The SRE curriculum that was introduced in Tanzania in primary schools during early 2000's in response to the control of HIV epidemic has been important for adolescents in primary and secondary schools, but the challenge is the inability of some of the teachers to deliver the message and topics clearly (34). Mkumbo (2012) showed majority of urban and rural teachers are in favour of teaching SRE (12), but Cardoso and Mwolo noted ineffective inclusion of sensitive sexuality matters in the school curricula (34).…”
Section: Discussionmentioning
confidence: 99%
“…The SRE curriculum that was introduced in Tanzania in primary schools during early 2000's in response to the control of HIV epidemic has been important for adolescents in primary and secondary schools, but the challenge is the inability of some of the teachers to deliver the message and topics clearly (34). Mkumbo (2012) showed majority of urban and rural teachers are in favour of teaching SRE (12), but Cardoso and Mwolo noted ineffective inclusion of sensitive sexuality matters in the school curricula (34). Such curriculums lack enough resources and the students do not appreciated much the school as a tutor for sexual health matters.…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania, the provision of sexual health care is focused on HIV and STI services, sexual and reproductive health care such as use of contraceptives, youth pregnancies and post abortion care, management and prevention of female genital mutilation/cutting (FGM/C), treatment of sexual dysfunction, management of sexual violence and sexual-related problems among key populations including sex workers (SW) and men who have sex with men (MSM), and provision of non-formal sex education (Cardoso & Mwolo, 2017 [Tanzania], 2017). Countries in Sub-Saharan Africa are faced with multiple challenges in their health care systems that act as barriers to provision of health care, and in particular to the delivery of sexual health care (Akatukwasa et al, 2019;Jonas et al, 2018;Oleribe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%